AquaNet - Chemical parameters from Erken AquaNet platform - Erken Laboratory (Uppsala University, 2020)
Data contains chemical parameters from grab samples taken from the AquaNet mesocosms.
Erken Laboratory (2020). AquaNet - Chemical parameters from Erken AquaNet platform, 2017-06-13–2017-09-11 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/wj4L8CcxnkxeTtZ75HZNe9vq
Keywords: SITES; Chlorophyll; Fish; Nitrogen Compounds; Phosphorous Compounds; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap